(untitled) (Nursing Sciences Journal, 2023)
Students are at high risk of emergencies as various incidents can occur within this group. Additionally, children spend significant time at school, increasing their risk of injury. Emergencies can happen unexpectedly and anywhere, including at home, on the road, and within the school environment. Most injuries in children are directly related to physical activities outside, with many injuries occurring during school hours. This study was quasi-experimental, focusing on one group without randomization. The design employed a pre-and post-test approach using the Wilcoxon test. The study was conducted in May 2023 with 38 respondents. Results: Based on the results, the "good" category, which initially had 0% of respondents, became 100%, while the "poor" category, which initially had 89.5% of respondents, became 0%. The knowledge score of teachers improved from 0.001 before receiving the JATUR Booklet to 0.002 after receiving it. Thus, it can be concluded that there is a difference before and after the intervention of providing the booklet, with a non-normal distribution (p0.05). There is an increase in knowledge scores after providing the Falling and Injured (JATUR) First Aid Booklet.